Parapharyngeal Abscesses Caused by Group G Streptococcus. (27th September 2018) - Tajima, Shori; Anzai, Takashi; Matsuoka, Rina; Okada, Hiroko; Ide, Takuma; Fujimaki, Mitsuhisa; Kaya, Shota; Ito, Shin; Ikeda, Katsuhisa
Abstract : Deep neck abscess is a life-threatening infection that causes laryngeal edema and upper airway occlusion. The predominant bacterial species involved in this disorder is group A streptococcus. Group G streptococcus (GGS) constitutes the normal commensal flora of the human upper airway. Although rarely, it can cause pharyngitis, tonsillitis, and peritonsillar abscess. Here, we report a case of a woman with parapharyngeal abscess caused by GGS. A 56-year-old woman presented to the emergency department with complaints of sore throat and cervical swelling, and a diagnosis of parapharyngeal abscess was established. She had upper airway occlusion, requiring urgent tracheostomy. Endoscopic incision and drainage of the abscess using a specially designed, rigid curved laryngoscope was successfully performed. Since a rigid curved laryngoscope creates a wide viewing field and working space, it was useful for incision and drainage of the parapharyngeal abscess.